2019
DOI: 10.1007/s12182-019-00411-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation on hydrodynamics of non-spherical particulate system using a drag coefficient correlation based on artificial neural network

Abstract: Fluidization of non-spherical particles is very common in petroleum engineering. Understanding the complex phenomenon of non-spherical particle flow is of great significance. In this paper, coupled with two-fluid model, the drag coefficient correlation based on artificial neural network was applied in the simulations of a bubbling fluidized bed filled with non-spherical particles. The simulation results were compared with the experimental data from the literature. Good agreement between the experimental data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…We can see that the profiles of higher sphericity particle exhibit flat and uniform since their interlock forces are less than those of lower sphericity particles. 38 , 39 Lower sphericity ultralight particles are sensitive to followability by the gas phase rather than controlled by their own inertia leading to the complex transport characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We can see that the profiles of higher sphericity particle exhibit flat and uniform since their interlock forces are less than those of lower sphericity particles. 38 , 39 Lower sphericity ultralight particles are sensitive to followability by the gas phase rather than controlled by their own inertia leading to the complex transport characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The most important phenomenon observed is that the peak values of ψ = 0.63 and 0.72 are approximately 3.0 times larger than those sphericities located at near central regions (see Figure a). It is demonstrated that the drag force for the higher irregular-shaped degree is far greater than the interlock force between particles and their own centrifugal force. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying more complicated methods, such as quadratic expressions or artificial neural networks (ANNs), can achieve a better prediction by considering nonlinear behavior . The ANN is one machine learning method that can effectively predict systems without needing to use casual models and has been applied to various applications. Whereas the parameters from the ANN do not have physical meaning, the quadratic expressions make it possible to interpret the interactions between independent variables. A least absolute shrinkage and selection operator (LASSO) method, another machine learning-based technique, can be applied to the quadratic equations to achieve high prediction accuracy and interpretability by excluding minor coefficients. …”
Section: Introductionmentioning
confidence: 99%